ASSESS THE AWARENESS REGARDING GENDER DISCRIMINATION AMONG THE MEDICAL PROFESSIONALS WORKING IN HOSPITALS AND MEDICAL COLLEGES IN RURAL INDIA. - Sanjeev G. Gianchandani; Bhushan Patil; Dr Kunal Rawekar; Gayatri S. Dhapudkar; Payal S. Wankhade; Grishma R. Chetty (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Discrimination against women has always existed in the world and, regrettably, still does in many forms.The denial of opportunity, equality, or both because of a person's gender is known as gender discrimination. There is no gender distinction in nature. However, discrimination against women has a global impact in terms of employment opportunities as well as social and political rights. Women in India are routinely discriminated against. Most women are unaware of their rights. There are many aspects of life where women are denied opportunities. This study is aimed at assessing awareness of gender discrimination in medical professionals working in hospitals and medical colleges in the district of Wardha, a rural area of India.Aims and Objective:• To determine the awareness of society of gender inequality in medical professionals.• To evaluate the results using particular demographic factors.Materials and Methods: 200 participants in the current descriptive study are drawn from the general population of Wardha using a non-probability convenience sampling technique. An attitude score regarding the awareness of gender discrimination in medical professionals was recorded. It was categorized as very low, low, average, good, and exceptional depending upon the score ranging from 0 to 100.Results: The outcome revealed that none of them had a very low (0 to 20) or low(21 to 40) attitude score, an average attitude score (41 to 60) was recorded in 31 percent participants, a good attitude score between 61 to 80 was recorded in the majority 68.5 percent of participants , furthermore, none of the participants had an excellent attitude score. The mean score was 62.66 ±31.33% . In summary the average populace in rural areas is not entirely aware of gender discrimination amongst the medical professionals. It was shown that demographic factors had little bearing on the general public's awareness of gender discrimination.